2019
DOI: 10.1111/fwb.13362
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes in the biomass, distribution, and patchiness of zooplankton and fish in four lakes in the Sierra Nevada, California

Abstract: Zooplankton are important components of lentic ecosystems, affecting phytoplankton, water clarity, and nutrient cycling, as well as transferring primary production to upper trophic levels. Many of these processes are temporally and spatially heterogeneous, but are difficult to observe at fine scales with traditional sampling methods. High‐resolution sampling has been especially rare in remote and high‐altitude lakes. We measured the vertical distribution of zooplankton and fish in four lakes in the Sierra Neva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 83 publications
(107 reference statements)
0
1
0
Order By: Relevance
“…1). Higher elevation lakes exhibit lower nutrient and DOC concentrations than mid-elevations lakes (Moser et al 2019;Urmy and Warren 2019); in this area, microbial activities may be constrained by nutrient concentrations. Previous studies have found that alpine ecosystems are highly sensitive to modest N deposition (Baron et al 2000;Wolfe et al 2003;Vinebrooke et al 2014).…”
Section: Relationships Between Methane Organic Matter Production and ...mentioning
confidence: 96%
“…1). Higher elevation lakes exhibit lower nutrient and DOC concentrations than mid-elevations lakes (Moser et al 2019;Urmy and Warren 2019); in this area, microbial activities may be constrained by nutrient concentrations. Previous studies have found that alpine ecosystems are highly sensitive to modest N deposition (Baron et al 2000;Wolfe et al 2003;Vinebrooke et al 2014).…”
Section: Relationships Between Methane Organic Matter Production and ...mentioning
confidence: 96%